HUBUNGAN PERAN PERAWAT SEBAGAI CARE GIVER DENGAN LENGTH OF STAS (LOS) DI IGD UPTD PUSKESMAS MUBUNE KECAMATAN LIKUPANG BARAT - Rompas, Jois (Journal Of Community & Emergency, 2024)
The role of nursing care giver is the most important role for a nurse. In this role, nurses are expected to be able to provide nursing services to individuals according to the diagnosis of problems that occur. Late treatment process and LOS patients in IGD is the key to measuring the occurrence of overcrwoded in IGD.. The purpose of this study is known to be the relationship of the role of nurses as care givers to length of stay (LOS) in IGD UPTD Puskesmas Mubune West Likupang Subdistrict. The type of research used is research using Cross Sectional research design. The population in this study is a nurse who served in the Emergency Department of UPTD Mubune Health Center likupang subdistrict and a sample of 32 samples. The data was analyzed using statistical tests with an meaningful rate of 95% (α): 0.05. Based on the results of the test using the chi-square test obtained the value p = 0.001 for that means the value of p = 0.001 is less than the value of α = 0.05. Then Ho was rejected which means there is a relationship between the role of nurse as a care giver with length of stay (LOS) in IGD UPTD Puskesmas Mubune. The conclusion in this study is to show that the results of the distribution of the role of nurses as care givers, known most of the roles of nurses in the category are not good. The distribution of length of stay (LOS) in the category is not appropriate. There is a relationship of the role of nurses as care givers with length of stay (LOS) in IGD UPTD Puskesmas Mubune West Likupang Subdistrict